The Road to Infection: Host-Microbe Interactions Defining the Pathogenicity of Streptococcus bovis/Streptococcus equinus Complex Members - Jans, Christoph; Boleij, Annemarie (Frontiers in Microbiology, 2018)
The Streptococcus bovis/Streptococcus equinus complex (SBSEC) comprises several species inhabiting the animal and human gastrointestinal tract (GIT). They match the pathobiont description, are potential zoonotic agents and technological organisms in fermented foods. SBSEC members are associated with multiple diseases in humans and animals including ruminal acidosis, infective endocarditis (IE) and colorectal cancer (CRC). Therefore, this review aims to re-evaluate adhesion and colonization abilities of SBSEC members of animal, human and food origin paired with genomic and functional host-microbe interaction data on their road from colonization to infection. SBSEC seem to be a marginal population during GIT symbiosis that can proliferate as opportunistic pathogens. Risk factors for human colonization are considered living in rural areas and animal-feces contact. Niche adaptation plays a pivotal role where Streptococcus gallolyticus subsp. gallolyticus (SGG) retained the ability to proliferate in various environments. Other SBSEC members have undergone genome reduction and niche-specific gene gain to yield important commensal, pathobiont and technological species. Selective colonization of CRC tissue is suggested for SGG, possibly related to increased adhesion to cancerous cell types featuring enhanced collagen IV accessibility. SGG can colonize, proliferate and may shape the tumor microenvironment to their benefit by tumor promotion upon initial neoplasia development. Bacteria cell surface structures including lipotheichoic acids, capsular polysaccharides and pilus loci (pil1, pil2 and pil3) govern adhesion. Only human blood-derived SGG contain complete pilus loci and other disease-associated surface proteins. Rumen or feces-derived SGG and other SBSEC members lack or harbor mutated pili. Pili also contribute to binding to fibrinogen upon invasion and translocation of cells from the GIT into the blood system, subsequent immune evasion, human contact system activation and collagen-I-binding on damaged heart valves. Only SGG carrying complete pilus loci seem to have highest IE potential in humans with significant links between SGG bacteremia/IE and underlying diseases including CRC. Other SBSEC host-microbe combinations might rely on currently unknown mechanisms as comparative genome data of blood, commensal and food isolates are limited but required to elucidate the role of pili and other virulence factors, understand pathogenicity mechanisms, host specificity and estimate health risks for animals, humans and food alike.